Current Cost Accounting and the Nationalised Industries: An Analysis and a Proposal (Book). - Perks, Robert W.; Hendrickson, Harvey S. (The Accounting Review, 1985)
Reviews the book "Current Cost Accounting and the Nationalised Industries: An Analysis and a Proposal," by Murray C. Wells.